PENGARUH MEDIA BUKU CERITA BERGAMBAR TERHADAP PERKEMBANGAN BAHASA ANAK KELOMPOK B DI TK TADIKA PURI SURABAYA - Nindiya Restu ningtyas; Rachma Hasibuan (LPPM Universitas Negeri Surabaya, 2023)
Language skills are one of the abilities developed in early childhood education. This research is motivated by the low language skills of children at the school. This study aims to determine the effect of learning media with picture books on children's language skills. This research used a quantitative approach with the type of pre-experimental research with a one-group pretest-posttest design. The data technique used a non-parametric statistical level test using Wilcoxon with the formula t count <t table. If tcount <ttable, this research is significant. The results of the Wilcoxon test analysis obtained tcount = 0 <ttable = 35. If the tcount <ttable with a significant level of 5%, namely 0 <35, then Ha is accepted and Ho is rejected. So it can be denied that the picture book media has an effect on the language of group B children at TK Tadika Puri Surabaya. Keywords: Picture Book Media; Language Skills; Early Childhood